2019
DOI: 10.1002/hbm.24563
|View full text |Cite
|
Sign up to set email alerts
|

Illusory own body perceptions mapped in the cingulate cortex—An intracranial stimulation study

Abstract: Body awareness is the result of sensory integration in the posterior parietal cortex; however, other brain structures are part of this process. Our goal is to determine how the cingulate cortex is involved in the representation of our body. We retrospectively selected patients with drug‐resistant epilepsy, explored by stereo‐electroencephalography, that had the cingulate cortex sampled outside the epileptogenic zone. The clinical effects of high‐frequency electrical stimulation were reviewed and only those sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…This result is also in contrast with Simon et al (2013), who found that the precentral gyrus of both trans women and trans men do not differ from controls sharing the same gender identity. Moreover, we found weaker FC in trans men versus cis men in the cingulate gyrus, a brain area involved in body perception (Popa et al, 2019), and in structures engaged in the Default Mode Network (DMN) such as the paracingulate gyrus and the subcallosal cortex, which is engaged in cognitive and emotional processes (Mayberg et al, 2008). These areas are in uenced by hormone therapy and especially within the subcallosal cortex trans women showed a deactivation during estradiol treatment (Schenider et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This result is also in contrast with Simon et al (2013), who found that the precentral gyrus of both trans women and trans men do not differ from controls sharing the same gender identity. Moreover, we found weaker FC in trans men versus cis men in the cingulate gyrus, a brain area involved in body perception (Popa et al, 2019), and in structures engaged in the Default Mode Network (DMN) such as the paracingulate gyrus and the subcallosal cortex, which is engaged in cognitive and emotional processes (Mayberg et al, 2008). These areas are in uenced by hormone therapy and especially within the subcallosal cortex trans women showed a deactivation during estradiol treatment (Schenider et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It also appears to be specifically related to both interoceptive and exteroceptive perception, including sense of self-location and direction (Guterstam et al, 2015), and altered states of bodily awareness, such as body illusions (Park et al, 2016). A case study found that a tumor in the PCC was associated with symptoms consistent with depersonalization (Hiromitsu et al, 2020) and similarly, stimulation of the region has been associated with the perception of limb movement when at rest (Popa et al, 2019). The isthmus is adjacent and posterior to the PCC; it connects the PCC to the parahippocampal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Given the recent interest in neuromodulation, our findings apply to the clinic. Several neurological deficits have been linked to vestibular malfunctioning [14,[23][24][25]. Because the Cingulate Gyrus is involved in vestibular processing, this region provides an inviting potential target for treating several disorders.…”
Section: Clinical Potentialmentioning
confidence: 99%